Water Conservation Science and Engineering - Water Conservation Science and Engineering (Springer Nature, 2026)
Water Conservation Science & Engineering targets the developing multidisciplinary areas in sciences and engineering associated with water conservation. The journal welcomes original contributions, potentially involving multidisciplinary research, that consider sustainable management and conservation of water as a valuable resource.
FI 0.25
Q4
Keywords: Earth; Space & Environmental Sciences; Sustainable Development; Ciencias de la tierra; Desarrollo sustentable; Acuerdos transformativos; Transformative agreements; Conservación del agua; Hidrología; Ciencia del agua